Echoing the effect of information and communications technology on rural education development - Oki, Olukayode Ayodele; Uleanya, Chinaza; Mbanga, Sanelisiwe (Technology audit and production reserves, 2023)
Information and Communications Technology (ICT) is crucial to teaching and learning as it has effect on such exercises in schools. However, ICT is limited in rural based compared to urban schools. In this study, the effect of the incorporation of ICT on the academic performance of rural secondary school students was investigated. Quantitative method was adopted for the study. The sample of the study comprised 34 matric learners and 14 teachers from three selected secondary schools in the rural Cofimvaba District of the Eastern Cape Province), South Africa. Questionnaire was used as the instrument for data collection. Excel was the software used to analyze the results. The findings showed that ICT use can indeed have a positive impact on learners’ academic performance. Some teachers, however, suggested that certain measures be put in place through using ICT to encourage positive behaviour. The study recommends that all rural and urban secondary schools should have access to the relevant ICT and ICT device, as these aid teaching and learning.